Uji Perbandingan Efektivitas Antibakteri Pasta Gigi Komersial Berbahan Daun Sirih, Siwak Kombinasi atau Lidah Buaya Terhadap Staphylococcus Aureus - Edon, Cindy Marie Agnes Lorenza Aurelia; Pakan, Prisca Deviani; Lada, Christina Olly (Cendana Medical Journal, 2023)
Abstract Background: Dental health problem if not treated will cause coronary heart disesase and stroke. Toothpaste products are widely marketed to be antibacterial substances, by adding herbal active ingredient including betel leaf, siwak combination, or aloe vera. Research Objectives: To compare the antibacterial efficacy of commercial toothpaste with betel leaf, siwak combination, or aloe vera active components against Staphylococcus aureus. Research Methods: This study used a quasi-experimental design method with posttest–only nonequivalent control group design. The treatment group consisted of a commercial toothpaste containing the active ingredients betel leaf, siwak combination or aloe vera as well as positive control of non-herbal toothpaste, and negative control of sterile distilled water as a comparison with five repetitions for each treatment group of Staphylococcus aureus bacteria. The data was analyzed using the One Way ANOVA statistical test, which had a 95% confidence level. Positive inhibitory zone is characterized by a clear zone with a diameter of 5-20 mm. Results: The One Way ANOVA analysis test showed p-value = 0.000 where there were significant differences between the treatment groups. Betel leaf toothpaste (9.44 mm) in medium category, siwak combination (13.28 mm) with strong category or aloe vera (18.24 mm) with strong category. Conclusion: Toothpaste with active ingredients of betel leaf, siwak combination, or aloe vera have different antibacterial properties Keywords: Toothpaste, Inhibitory, Antibacterial